Motor cortex electric stimulation for the treatment of neuropathic pain - Walter J. Fagundes-Pereyra; Manoel Jacobsen Teixeira; Nicolas Reyns; Gustavo Touzet; Sérgio Dantas; Emmanuelle Laureau; Serge Blond (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Motor cortex stimulation (MCS) is considered to be an effective treatment for chronic neuropathic pain. The aim of the present study was to assess the efficacy of MCS for treating neuropathic pain. METHOD: 27 patients with chronic neuropathic pain were operated. Electrodes were implanted with the use of an stereotactic frame. Electrophysiological evaluations (motor stimulation and somatosensory evoked potentials) were performed, with guidance by means of three-dimensional reconstruction of magnetic resonance images of the brain. 10 patients (37%) presented central neuropathic pain (post-stroke pain) and 17 others (63%) presented peripheral neuropathic pain (brachial plexus avulsion, phantom limb pain or trigeminal pain). RESULTS: In 15 patients (57.7%) the pain relief was 50% or more; while in ten patients (38.5%), more than 60% of the original pain was relieved. No differences were found in relation to central and peripheral neuropathic pain (p=0.90), pain location (p=0.81), presence of motor deficit (p=0.28) and pain duration (p=0.72). No major complications were observed. CONCLUSION: MCS was efficient for treating patients presenting chronic central or peripheral neuropathic pain.